2013
DOI: 10.1021/jp308879r
|View full text |Cite
|
Sign up to set email alerts
|

Site Specificity on OH α-H Abstraction Reaction for a Zwitterionic β-Hairpin Peptide in Aqueous Solution: A Theoretical Investigation

Abstract: Protein backbone oxidation was investigated by studying the α-H abstraction reaction in a ß-hairpin peptide, called Chignolin (PDB ID 1UAO), with density functional theory calculation at B3LYP/6-31G(d,p) without any constraint. In order to stabilize the zwitterionic form of Chignolin with the salt bridges, the effects of aqueous solution were implemented by using microsolvation combined with a conductor-like polarizable continuum model (CPCM). Comparison between three glycine residues located at three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…For example, Rauk and coworkers used density‐functional‐theory calculations to show that conformational differences can have a substantial effect on the α‐CH bond dissociation energies . In addition, Li and coworkers have examined the conformational effects for α‐radical formation in a small naturally occurring peptide . Investigations of a similar nature have helped to unravel the effects on kinetics in other cases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Rauk and coworkers used density‐functional‐theory calculations to show that conformational differences can have a substantial effect on the α‐CH bond dissociation energies . In addition, Li and coworkers have examined the conformational effects for α‐radical formation in a small naturally occurring peptide . Investigations of a similar nature have helped to unravel the effects on kinetics in other cases .…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, direct calculations on the full peptide radicals and their parent peptides would provide the most accurate computational approach to this problem. This is indeed the methodology used by Li and coworkers, who used density‐functional‐theory (DFT) methods [e.g., B3‐LYP/6‐31G(d) to study the radical chemistry of a 10‐residue small peptide. While advances in quantum chemistry methodologies and computing technologies have made it possible to carry out explicit DFT computations for even larger molecules, a significantly more efficient strategy would be to use a multilayer approach such as the ONIOM method of Morokuma and coworkers …”
Section: Introductionmentioning
confidence: 99%
“…Several computational studies investigated the H abstraction reaction, 22,[24][25][26][27][28][29][30]31,33,42,43,[48][49][50][51][52][53][54][55][56][57] focusing mainly on glycine and alanine. Galano et al employed different levels of theory to characterize the reaction in the gas-phase.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Rauk et al observed that the b-sheet conformation favors the radical attack due to a larger captodative effect. 54 The effect that the protein conformation has on the reaction has also been investigated in two different 10 residue-long proteins, chignolin 56 and b-hairpin. 57 The attack of the OH radical on other amino acids has also been investigated, including asparagine, 31 serine, 22 methionine, 48 leucine, 50 isoleucine 30 or proline.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the alpha-carbon is consistently a competitive site of • OH attack. Lin et al investigated hydrogen abstraction in a β-hairpin peptide . Molecular dynamics was used to sample peptide conformations, and ab initio methods are used to determine energies and to examine the potential energy surface along the reaction pathway.…”
Section: Introductionmentioning
confidence: 99%